2019
DOI: 10.1002/etc.4521
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and Sublethal Toxicity of Thiamethoxam and Clothianidin Commercial Formulations to Soil Invertebrates in a Natural Soil

Abstract: The use of neonicotinoids in agriculture is a critical environmental protection issue. Although there has been considerable research on pollinator exposure and aquatic toxicological effects, few studies have investigated the chronic impacts on soil‐dwelling species. Given the application of neonicotinoids into soil systems, there is the potential for risk to soil invertebrates. The toxicity of 2 commercial formulations containing the active ingredients (a.i.) thiamethoxam (Actara® 240SC) or clothianidin (Titan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
12
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
5
12
5
Order By: Relevance
“…Clothianidin was approximately 100 times more toxic than thiacloprid, with an LC50 of 0.07 mg a.s./kg dry soil. Ritchie et al (2019) tested the commercial formulation Titan ® (clothianidin) to F. candida, and their results are similar to ours, indicating that toxicity of the pure active substance (a.s.) is not affected by formulating agents.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Clothianidin was approximately 100 times more toxic than thiacloprid, with an LC50 of 0.07 mg a.s./kg dry soil. Ritchie et al (2019) tested the commercial formulation Titan ® (clothianidin) to F. candida, and their results are similar to ours, indicating that toxicity of the pure active substance (a.s.) is not affected by formulating agents.…”
Section: Discussionsupporting
confidence: 77%
“…Residues of clothianidin were confirmed in soil samples taken at the end of the test (56 d), indicating that thiamethoxam was indeed converted into clothianidin in our earthworm tests. Ritchie et al () also found residues of clothianidin in the tests performed with thiamethoxam, using E. andrei as a surrogate. In their results, concentration of clothianidin increased over time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Firefly larvae of other species are known to feed on slugs ( Barker, 2004 ), which can also contain high doses of neonicotinoids (500 ng g −1 ), leading to disrupted biological control provided by carabid beetles ( Douglas, Rohr & Tooker, 2015 ). Compounded with reduced prey availability in habitats where neonicotinoids are used ( Ritchie et al, 2019 ; Tooker & Pearsons, 2021 ), decreased feeding activity and high risks of further neonicotinoid exposure through contaminated prey may explain why adult lampyrid densities are significantly lower where clothianidin has been used as a seed coating ( Disque et al, 2019 ), even if acute mortality is low. Adult fireflies may also encounter neonicotinoid residues while resting on sprayed vegetation or during oviposition into soil ( Pisa et al, 2021 ), although the risk of such exposure does not appear to have been explored.…”
Section: Discussionmentioning
confidence: 99%
“…equation.proved that imidacloprid was more toxic than thiacloprid on Eisenia andrei Ritchie et al (2019). investigated that exposure to clothianidin resulted in a 56-d LC50 of 0.26 mg kg -1 dry soil for E. andrei.…”
mentioning
confidence: 99%